Leptin as an important link between obesity and cardiovascular risk factors in men with acute myocardial infarction - Ekmen, Nergis (Indian Heart J, 2016)
OBJECTIVE: The levels of leptin, a major regulator of lipid metabolism, may increase in obesity, and contribute to the development of metabolic syndrome. Leptin is produced by adipose tissue and is a peptide hormone, which has strong association with obesity, elevated cardiovascular risk, and morbidity. The present study was designed to evaluate the relationships between leptin levels, obesity, and cardiovascular risk factors in men with acute myocardial infarction. METHODS AND RESULTS: Twenty-four obese and twenty-three nonobese male patients, who had experienced their first myocardial infarction, were included in the study. Their leptin levels, biochemical parameters, and anthropometric measures were obtained. Mean leptin levels were significantly higher in the obese group compared to the nonobese group (2.53 ng/mL versus 1.23 ng/mL; p < 0.01). Leptin levels correlated positively with anthropometric measurements, triglyceride, fasting glucose, C-reactive protein, and uric acid levels, and negatively with high-density lipoprotein cholesterol levels. CONCLUSION: Findings indicate high leptin levels to be positively correlated with obesity and diastolic blood pressure in male patients with myocardial infarction.